Thermal fatigue resistance characterization and ranking of materials using the V‐shape specimen testing method. (7th February 2014) - Wei, Z.; Konson, D.; Yang, F.; Luo, L.; Lin, B.; Ellinghaus, K.; Pieszkalla, M.
ABSTRACT Thermal fatigue resistance of materials is an extremely important criterion for the long‐term durability and reliability performance of very high‐temperature components and systems, such as advanced auto engine and exhaust systems. There is a broad range of material choices for thermal fatigue resistance applications. The final selection of the materials depends on the balance of engineering performance of the materials and the cost. To optimize the thermal fatigue resistance and cost of those materials, a reliable testing procedure for material thermal fatigue characterization and a material evaluation/selection matrix must be established. In this paper, the V‐shape specimen testing method in evaluating thermal fatigue resistance performance is introduced first. The influence of several factors, such as the thickness of specimens, operating temperature and hold time, on the thermal fatigue resistance is experimentally investigated. Subsequently, the statistical and probabilistic characteristics of the thermal fatigue failure data are analysed to reveal the possible failure mechanisms. Finally, a general rational approach for thermal fatigue resistance characterization and ranking is demonstrated, and a simple parameter λ = kσf/Eα, which combines the material strength, thermal conductivity and thermal expansion, is found to be the new breakthrough parameter, correlating to V‐shape thermal fatigue test results. Results on four currently used stainless steels verify the correlations and indicate the validity of this approach.